Strategi Pengembangan Kedisiplinan Siswa di SMA N 1 Tanjung Mutiara - Musnaini Musnaini; Hidayani Syam (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The purpose of this research is to provide suggestions to help students become more disciplined. This research uses a descriptive qualitative approach. Teachers and students at SMA N 1 Tanjung Mutiara were used as research subjects. We used interview and observation techniques to collect data. Research findings include the strategy for developing discipline at SMA N 1 Tanjung Mutiara as follows: making a mission statement, vision statement and educational goals. regardless of the rules that apply at school. Because developing superior discipline requires applying that discipline both in the classroom and outside the classroom. The discipline of the children of SMA N Tanjung Mutiara is proof of the successful implementation and results of the program. grows in terms of self-control in behavior and friendships and study habits. There are more people who apply discipline well at school than those who don't, but there are still many people who do not apply discipline according to the school's wishes.